2019
DOI: 10.1002/ddr.21599
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of natural naphthoquinones as sortase A inhibitors and potential anti‐infective solutions against Staphylococcus aureus

Abstract: Three natural naphthoquinones were screened to find new anti‐virulence agents as inhibitors against sortase A from Staphylococcus aureus (SaSrtA) by quantifying the increase in fluorescence intensity upon substrate cleavage at various concentrations. The 5‐hydroxy‐1,4‐naphthalenedione derivatives, juglone and plumbagin, demonstrated a potent inhibitory effect, with IC50 values of 1.78 μM, respectively, 16.71 μM. The related 2‐hydroxy‐1,4‐naphthalenedione derivative, lawsone, demonstrated the selectivity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 42 publications
(50 reference statements)
0
22
0
Order By: Relevance
“…However, the most active compounds were found to be irreversible covalent inhibitors containing an electrophilic warhead that reacts with the active‐site Cys126 of SrtA . While having significant inhibition in the low micromolar range, they typically exhibit poor target selectivity or are cytotoxic such as quinones, rhodanines, or benzisothiazolinones . Zhulenkovs et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, the most active compounds were found to be irreversible covalent inhibitors containing an electrophilic warhead that reacts with the active‐site Cys126 of SrtA . While having significant inhibition in the low micromolar range, they typically exhibit poor target selectivity or are cytotoxic such as quinones, rhodanines, or benzisothiazolinones . Zhulenkovs et al .…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the determination, young daphnids were selected according to their size and maintained for 24 h in artificial medium. The bioassay was performed on 10 daphnids/replicates in tissue culture plates with 12 wells (Greiner Bio-One) according to the protocol described in our previous studies [ 50 , 51 ]. For each compound, six concentrations were tested, ranging from 5 to 128 µM.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibition kinetics and docking studies indicated an irreversible mechanism based on the Cys184’s thiol catalytic residue addition to the dual conjugated double system of the naphthoquinone structure. Lawsone, the 2-hydroxy-isomer of juglone, had no significant effect on Sa-SrtA at 10 μM because of its low reactivity towards nucleophilic agents [ 68 ]. The chemical structures of these naphthoquinone derivatives are presented in Figure 6 .…”
Section: Sortase a Inhibitorsmentioning
confidence: 99%